MENGEMBANGKAN KEMAMPUAN METAKOGNISI GURU PENDIDIKAN AGAMA KRISTEN UNTUK MENINGKATKAN PEMBELAJARAN DI KELAS - Onisimus Amtu; Esterlina Namserna; Claudia Monique Pattiruhu; Penina Romsery (Universitas Muria Kudus, 2021)
This study aims to find the ability of Christian religious education teachers to develop their metacognitive abilities to improve the quality of the process and learning outcomes in the classroom. The research focus is directed at three main aspects (1) the teacher's actions in overcoming the problems of Christian religious education learning, with five supporting indicators; (2) the appreciation of Christian religious education teacher metacognition in learning, with six supporting indicators; and (3) individual factors and social conditions of the metacognition process of Christian religious education teachers, with two supporting indicators. The research method used is a case study method with a qualitative approach, located at Ambon Senior High School 1 and 2, Maluku province. The data collection process used questionnaires, observations, interviews, and document studies involving Christian religious education teachers, students, school heads and school committees as informants to describe teachers' metacognitive abilities in learning in each school. The results of the study prove that the metacognitive abilities of Christian religious education teachers in learning at the high school level have been carried out well, while continuing to correct various deficiencies encountered in the learning process. With the knowledge of planning, monitoring and evaluation, it can be used to develop the learning process of Christian religious education. With the problems encountered in teaching Christian religious education in the classroom, the teacher continues to make improvements in the conceptual aspects of the material, learning methods or strategies as well as guidance in motivating students to learn well.